Test for the Production and Assay of the Proteolytic Activities of Halophilic Bacteria and Archaea Isolated from Algerian Hypersaline Environments - Hania Benmebarek; Juan-José Escuder-Rodríguez; María-Isabel González-Siso; Karima Karroub (Proceedings, 2020)
: The present work was carried out on 133 halophilic strains isolated on MGM (Modified Growth Medium) medium with 12 and 23% (w/v) of salt. A screening of the extracellular proteolytic activities, carried out on the same medium supplemented with casein or gelatin at 1% (w/v), allowed us to select 24 bacterial and 21 archaeal strains presenting a precipitate around the colonies for casein and/or a translucent halo (after addition of Frazier’s reagent) for gelatin. The enzymatic test was performed on liquid medium in microculture in a 2 mL Eppendorf tube. The assay of the proteolytic activity, using Azocasein as substrate, followed two protocols—the first with PBS and the second with Tris HCl, with positive and negative controls—and demonstrated interesting results for 10 strains among the 45 tested including five bacteria and five archaea. These underwent morphological, physiological and molecular characterizations based on amplification and sequencing of the 16S ribosomal RNA gene.